Analysis of the Social Networks by Means of the Vision of the Educative Community from a Micro-political Perspective - Juan Manuel Trujillo Torres; María Pilar Cáceres Reche (Universidad Autónoma de Madrid, 2016)
At the present, to recognize the value of the establishment of communitarian collaborative networks has become a necessity at the same time that it is an opportunity for improvement of the development dynamics of the educative organizations. However, in many occasions, those collaborative processes are not completely translucent therefore, a micro-political vision for their understanding and apprehension seems opportune. This analysis consequently may offer some enlightenment and reflect on and warn on the shadows that may limit the innovation and improvement processes of our educative centers. Our study is an example of it through an ethnographic research process.